PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA GURU - Alan Alfiansyah Putra Karo-Karo; Liliana Puspa Sari; Dicky Hendrawan (Jurnal Penjaskesrek, 2020)
The principal is expected to be able to increase the motivation of teachers to be able to become professional teachers and be able to compete in the world of education. The purpose of this study was to study the motivation of principals' leadership, and the motivation of vocational high school level teachers in Serdang Bedagai District. With a total sample of 30 physical education teachers from 30 schools in Serdang Bedagai Regency. Research uses quantitative with the method of Ex-Post Facto to find out and uncover data from past events and then study the factors that can cause these events. The results of the analytical research stated (1) the Relationship between Principals' Leadership to Teacher Performance by 0.539, (2) the effect of teacher's work motivation on Teacher Performance by 0.397, (3) there was a direct relationship between Principal's Leadership and Teacher's work motivation to Teacher Professionalism with total influence amounted to 0.753. The conclusion is the low performance of Physical Education at the Vocational School level in Serdang Bedagai Regency is supported by many factors including good Principal Leadership, and high Teacher Work Motivation. Abstrak Kepala sekolah yang baik diharapkan mampu meningkatkan motivasi kerja guru agar mampu menjadi guru profesioal dan mampu bersaing di dunia pendidikan. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh kepemimpinan kepala sekolah, dan motivasi guru tingkat sekolah menengah kejuruan di Kabupaten Serdang Bedagai. Dengan jumlah sampel sebanyak 30 orang guru pendidikan jasmani dari 30 sekolah di Kabupaten Serdang Bedagai. Penelitian menggunakan pendekatan Kuantitatif denganmetodeExt-Post Facto untuk mengetahui dan mengungkap data dari peristiwa-peristiwa yang telah lalu kemudian mengetahui faktor-faktor yang dapat menimbulkan kejadian tersebut. Hasil penelitian analisis jalur menyatakan bahwa (1) pengaruh Kepemimpinan Kepala Sekolah terhadap Kinerja Guru sebesar 0,539, (2) terdapat pengaruh Motivasi Kerja guru terhadap Kinerja Guru sebesar 0,397, (3) terdapat hubungan langsung antara Kepemimpinan Kepala Sekolah dan Motivasi kerja guru terhadap Profesionalisme Guru dengan pengaruh total sebesar 0,753. Kesimpulannya bahwa tinggi rendahnya kinerja guru Penjas tingkat SMK di Kabupaten Serdang Bedagai didukung oleh banyak faktor antara lain Kepemimpinan Kepala Sekolah yang baik, dan Motivasi Kerja Guru yang tinggi. Kata Kunci: Kepemimpinan, Motivasi, Kinerja, Guru